Considerations on handling link errors in SCTP - Irene Rüngeler; Michael Tüxen; Erwin P. Rathgeb (Universität Duisburg-Essen, Institut für Informatik und Wirtschaftsinformatik (ICB), 2009)
Today wireless network connections gain more and more importance. Yet a drawback of this technology is the higher packet error rate compared to wired networks. This has a negative impact on SCTP associations as packet loss is considered a congestion indication. The SCTP extension PKTDROP reacts to the notification of corrupted frames and circumvents the congestion control mechanism by retransmitting lost packets without changing the congestion window. In this paper we will point out the difference between TCP and SCTP due to message-orientation of SCTP and provide a formula to predict the throughput of an error-prone link, which can be beneficially applied for network planning. The validation of the PKTDROP extension will show that the effects of lossy links on the throughput can be fully compensated by this feature.
Keywords: 650; SCTP; packet loss; PKTDROP reporting; theoretical throughput; Funktechnik; Telekommunikationsnetz